Legal Politics Implementing Jakarta Bay Spatial Arrangements in The Framework of Realizing Good Governance - Appe, Appe; Suganda, Atma (International Journal of Social Service and Research, 2023)
The aim of this research is to analyze the regulatory authority of the Provincial Government of DKI Jakarta in the spatial management of the Jakarta bay, as well as to analyze and find legal solutions regarding ideal legal politics in the spatial arrangement of the Jakarta bay which can create good government. This study uses a normative juridical legal approach. The data collection in this study used the technique of library research, observation and field research originating from primary, secondary and tertiary legal materials which were analyzed qualitatively normatively. The results of the study show that the Provincial Government of DKI Jakarta can propose the establishment of a special area in its territory to the Government which can be managed directly by the Central Government or can be managed jointly between the Central Government and the Provincial Government of DKI Jakarta in accordance with statutory provisions. The study of the ideal legal politics in the spatial arrangement of the Jakarta Bay, then this cannot be separated from the juridical considerations that form the basis for the formation or making of a statutory regulatio..